Clinical Characteristics and Endoscopic Findings of the Patients with Cirrhosis of the Liver in a Tertiary Care Centre in Eastern Nepal - Ghimire, Ram Hari (Journal of Nobel Medical College, 2016)
Background Studies on clinical characteristics and upper gastrointestinal endoscopic findings of the cirrhotic patients in a tertiary care centre are sparse from eastern region of Nepal. The aim was to profile these patients clinically and analyse the endoscopic findings. Material and Methods This was a cross-sectional analytical study carried out in the Department of Medicine of Nobel Medical College, Biratnagar from 30st September 2012 to 30th August 2013(one year). After admission, detail medical history and meticulous clinical examination was carried out in every patient with clinical diagnosis of cirrhosis of liver. Routine, biochemical, hematological, imaging and special investigations were sent as per clinical scenario. Upper gastrointestinal endoscopy was carried out in all patients. Basic descriptive statistics were used to present the data. Results A total of 104 patients were enrolled in our study. The mean age was 50.09 years ± 11.79 (Range 26-79), of which 60% were males. Almost 70% of the patients were from productive age group (31-70 years). All the patients were symptomatic. Chronic excessive alcohol consumption was the commonest cause of cirrhosis (80.76%). The major clinical presentations were ascites (83.65%) and jaundice (79.92%). Pedal edema was the commonest (85.6%) presenting sign. Diabetes mellitus and pneumonia were common comorbidities. Gastroesophageal varices were commonest (70.19%) endoscopic finding. Conclusion Cirrhotic patients presented late with complete decompensation in the form of ascites, jaundice and upper gastrointestinal bleeding from esophageal varices. Mostly people with productive age group were affected. Journal of Nobel Medical College Volume 5, Number 1, Issue 8, January-July 2016, 26-31